Feasibility of using tuberose (P. tuberosa L.) in horizontal subsurface flow constructed wetland for heavy metal removal from domestic wastewater. Issue 1 (30th August 2015) - Singh, Mohini; Srivastava, Rajeev K.
Abstract : Constructed wetlands (CW) are well known for removal of organics, suspended solids, nutrients, and bacteria. However, the information on removal of heavy metals and their sequestration in plants especially, the ornamental plants is very limited. In this experimental study, efficiency of horizontal subsurface‐flow constructed wetland (HSCW) planted with an ornamental species Polianthus tuberosa L . was evaluated for heavy metal sequestration in the phytomass. The plants were harvested during the peak standing crop in early September, divided into leaves, inflorescence, roots, and rhizomes, and analyzed for six trace elements (Cu, Zn, Ni, Al, Pb, and Fe). Metal concentrations decreased in the order of roots > rhizomes > leaves > inflorescence. The highest concentration in aboveground biomass were recorded for Al (3.66 mg kg −1 ) and Fe (1.35 mg kg −1 ), while the lowest concentration was recorded for Pb (0.06 mg kg −1 ). Belowground biomass also followed the same decreasing trend, the highest concentrations being recorded for Al (6.28 mg kg −1 ) with 5.78 mg kg −1 and 6.09 mg kg −1 concentration in rhizomes and roots, respectively. The lowest concentration in belowground biomass was recorded for Ni (0.28 mg kg −1 ) and Pb (0.17 mg kg −1 ). The belowground/aboveground concentration ratio ranged between 1.19 and 5.13 with an average value of 2.50. Due to average belowground/aboveground biomass ratio < 1, the belowground/aboveground standing stock ratios for all the metals were > 1 except Fe (0.79). The maximum values for bioconcentration factor (BCF) were found for Al and Zn 81.5 and 16.3, respectively. Biological accumulation factor (BAF) and transfer factor (TF) values were > 1 and <1, respectively for most of the heavy metals, which suggests their immobilization in the roots/rhizosphere and therefore, the species can be best suited for phytostabilization. The results of this study therefore provide the comprehensive information on sequestration of Cu, Zn, Ni, Al, Pb, and Fe in vegetation during domestic wastewater treatment in CW with horizontal subsurface flow. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 125–132, 2016